Characteristics and Deformation Mechanisms of Neogene Red-Bed Soft Rock Tunnel Surrounding Rock: Insights from Field Monitoring and Experimental Analysis - Jin Wu; Geng Cheng; Zhiyi Jin; Zhize Han; Feng Peng; Jiaxin Jia (Buildings)
This study focuses on Neogene red-bed soft rock tunnels in the Huicheng Basin, China. Through engineering geological investigation, remote wireless monitoring systems, and total station multi-parameter monitoring, the deformation characteristics of red-bed soft rock surrounding rock under high in situ stress environments and their influencing factors were systematically analyzed. The findings reveal that the surrounding rock deformation follows a three-stage evolutionary pattern of “rapid, slow, and stable”. Construction disturbances can disrupt the stable state, leading to “deep V-shaped” anomalies or double-step responses in deformation curves. Spatially, the deformation exhibits significant anisotropy, with the haunch area showing the maximum deformation (95 mm) and the vault the minimum (65–73 mm). Deformation stabilization requires 30–42 days, and a reserved deformation of 10 cm is recommended based on specifications. Mechanical behavior analysis indicates that the stress–strain curves of red-bed argillaceous sandstone are stepped, with increased confining pressure enhancing both peak and residual strengths, validating the necessity of timely support. The study elucidates a multi-factor coupling mechanism: rock mass classification, temporal–spatial effects (excavation face constraints and rheological properties), construction methods, in situ stress levels, and support timing (timely support during the rapid phase inhibits strength degradation) significantly influence deformation evolution. The spatiotemporal distribution of surrounding rock pressure shows that invert pressure increases most rapidly, while vault pressure reaches the highest magnitude, with construction disturbances triggering stress redistribution. This research provides theoretical and practical guidance for the design, construction optimization, and disaster prevention of red-bed soft rock tunnels.